A descriptive study on the perceptions of UPV-CAS female students towards feminism - Belen, Marian Davie
This is a gender study on the perceptions of UPV-CAS female students towards feminism. This study aims to describe the perceptions of UPV CAS female students on family, marriage, employment, rights and duties, feminism, feminist movement and feminists, contemporary Filipina and economics and politics, and tto determine if their perceptions are feminist in leaning. (p)The researcher conducted a survey by giving out questionnaires to UPV CAS female students. Moreover, gender-related materials in the library were also utilized such as books, magazines, journals, etc. The respondents were chosen through the stratified random sampling technique. (p)The study reveals that the responses, considering all year levels, do not seem to vary considerably. There has not been so much difference in their responses although younger students seemed quite conservative in their outlook in some matters. (p)the study also reveals that the respondents had a positive perception towards feminism since most of their responses on the items were feminist in leaning. Most of their responses indicate that women these days are more or less enjoying a favorable status in society, although they still believe that gender inequality still exists. Moreover, they think that feminism is still necessary for Filipinas.